Analysis of Decision in Case Number: 04/KPPU-M/2019 Concerning Alleged Violation of Article 29 of Law Number 5 of 1999 in conjunction with Article 5 of Government Regulation Number 57 of 2010 Regarding Delay in Notification of Acquisition of PT Citra Laut - Halimah Ginting (Universitas PGRI Madiun, 2026)
Acquisition is a form of external expansion undertaken by companies for various strategic purposes, such as expanding markets, strengthening core businesses, or gaining a foothold in foreign markets. This study discusses the case of the acquisition of shares by PT Wijaya Karya Beton, Tbk. of PT Citra Lautan Teduh on December 5, 2014. This acquisition resulted in PT Wijaya Karya Beton, Tbk. controlling 99.5% of the shares of PT Citra Lautan Teduh. Although legally valid, this acquisition raised issues due to the delay in notifying the Business Competition Supervisory Commission (KPPU), as stipulated in Article 29 of Law Number 5 of 1999 Jo. Article 5 of Government Regulation Number 57 of 2010. PT Wijaya Karya Beton, Tbk. should have submitted the notification no later than 30 days from the effective date of the acquisition, which was December 16, 2014. The administrative sanctions imposed by the KPPU for the late notification have drawn significant attention to the notification regulations in acquisition transactions. These regulations are one of the guarantees of transparency in preventing monopolistic practices and unfair business competition